Hubungan Karakteristik Keluarga dengan Perilaku Hidup Bersih dan Sehat di Sekolah - Lathifah, Nurul; Nu’im Haiya, Nutrisia; Ardian, Iwan; Rismatul Azizah, Intan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Clean and Healthy Living Behavior (PHBS) is a set of actions that people and the world can take to stay healthy by adopting healthy habits. PHBS is a big part of keeping people healthy and raising their quality of life, especially at school, where kids spend most of their time together. Schools play a big part in helping kids develop good habits because that's where they learn, make friends, and grow as people. PHBS is still being used in schools, but there are some problems. For example, some students don't know how important it is to be clean and healthy. The goal of the study was to find out how family traits are related to students' clean and healthy living habits at school.. Method: A total of 141 students took part in this study, which uses a cross-sectional research design and a simple random sample method. Family traits are the independent variable, and clean and healthy living behavior is the dependent variable. The chi-square test is used for analysis. Results A good rating for family traits was given by 68.1%, a sufficient rating of 22%, and a poor rating of 9.9%. A good rating for clean and healthy living habits was given by 70.9%, a sufficient rating of 18.4%, and a poor rating of 10.6%. With a p-value of 0.000, the link between family traits and living in a clean and healthy way is important. Conclusion: Conclusion: There is a relationship between family characteristics and clean and healthy living behavior at MA Negeri 2 Rembang School.